Nocturnal animals² - Liu, Aoyang (Nanyang Technological University, 2023)
Nocturnal Animals might not describe all of us, but the still and peacefulness of the night is something that will resonate with every one of us. Everyone finds a unique connection with an amusing something or someone. I find our feline friends especially quirky and cute, emotional, yet lacking the judgemental nature of people, walking alongside them during the dark of night, allows me to blend it, be free, and feel peaceful. Nocturnal Animals² are all of us, the very human nature of wanting to fit in, yet stand out. It is the absence of light, or attention, or judgment, or whatever unique circumstance. What we are looking for is actually a sense of belonging. Together with the company and familiarity (to me, represented by cats), it makes us feel comfortable and at ease.